New Insights about Pulmonary Epithelioid Hemangioendothelioma: Review of the Literature and Two Case Reports - Romeu Duarte Mesquita; Marta Sousa; Carmen Trinidad; Eugénia Pinto; Iosu Antón Badiola (Case Reports in Radiology)
Pulmonary epithelioid hemangioendothelioma (PEH) is a rare neoplasm of vascular origin. There are three different major imaging patterns identified in thoracic manifestation of epithelioid hemangioendothelioma: (1) multiple pulmonary nodules; (2) multiple pulmonary reticulonodular opacities; and (3) diffuse infiltrative pleural thickening. Radiographically, presence of bilateral multiple nodules is the most common pattern of presentation. The diagnosis is made on the basis of histopathological findings and confirmed by positive immunohistochemistry staining. Although the prognostic factors for PEH have not yet been well established, a better prognosis is usually associated with the multinodular pattern. We report two different imagological presentations of this rare disease, based on two institutional experiences, along with a review of the relevant literature.